Globalisation from below : exploring the economic development impacts of private Chinese SME investment in Accra, Ghana - Mullins, Donal (Trinity College (Dublin, Ireland). Department of Geography, 2015)
Relations with China are increasingly a key driver of economic development on the African continent. For example, in 2012 China was Africa’s largest trading partner with imports of $85.38 billion and exports of $113.1 billion (IMF data, January 2014). Furthermore, Chinese banks are financing numerous infrastructural projects across different African states through concessional loans. Chinese foreign direct investment (FDI) is also growing in the African continent, with a mixture of public and private ventures firms investing US$2.52 billion in African states in 2012, while the accumulated Chinese FDI stock in Africa stood at US$21.23 billion in 2012 (Deborah Brautigam blog September 2013).
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin